Penerapan Model Problem Based Learning Menggunakan Media Exe Learning untuk Meningkatkan Hasil Belajar dan Kerjasama Siswa Pada Materi Hidrokarbon - Iis Siti Jahro; Dimas Ridho (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to determine the increase in students learning outcomes that learned using problem based learning models using media exe learning on hydrocarbon material and correlation between the contribution of teamwork activies to improve student learning outcomes. The population all students of class X SMA Negeri 11 Medan with 8 classes. The sample taken two classes namely one class as the experimental class I who got teaching model of problem based learning using media exe learning and the  experimental class II who got teaching model of problem-based learning without media exe learning. In this study used test instrument and non-test instrumen. The test instrument that used 16 valid questions with the realibility of 0.85. The non-test instrument is used in the form of attitudes observasion sheet with indicator includes participation in learning, involvement and help peers. Based on the hypothesis test with significance level of 0.05 was tcount(4,285) > ttable(1,668). This mean Ha accepted and Ho rejected which showed an increase in student learning outcomes in the eksperimental class I higer than the eksperimental class II. Then the correlation test results indicating a positive correlation between the students teamwork activities with improving student learning outcomes that rcount(0,681) > rtable(0,320) with a coefficient of contribution 46.37%. Keywords: exe learning, problem based learning, teamwork, hydrocarbon